ChemInform Abstract: One‐Pot Multicomponent Synthesis of Highly Functionalized Bio‐Active Pyrano[2, 3‐c]pyrazole and Benzylpyrazolyl Coumarin Derivatives Using ZrO2 Nanoparticles as a Reusable Catalyst. Issue 38 (3rd September 2015) - Saha, Arijit; Payra, Soumen; Banerjee, Subhash
Abstract The catalyst is reusable up to ten cycles without loss of catalytic activity and its tetragonal plane.